PENGETAHUAN IBU HAMIL TENTANG PENTINGNYA PEMENUHAN KEBUTUHAN VITAMIN D UNTUK MENCEGAH PREEKLAMSIA DAN DIABETES GESTASIONAL SETELAH DIBERIKAN EDUKASI - Andriana Andriana (CV. ADIBA AISHA AMIRA, 2026)
Vitamin D deficiency is associated with the risk of preeclampsia and gestational diabetes in pregnant women. Insufficient level of knowledge affects the adequacy of mother's vitamin D needs during pregnancy. The aim of the research was to analyze differences in mothers' levels of knowledge before and after being given education. Quantitative research method, pre-experimental design, one group pretest posttest on 50 pregnant women for 6 days. The research results showed differences in the level of knowledge of pregnant women before and after being given education with a p value of 0.000 <0.05. In conclusion, the level of knowledge of pregnant women about the importance of meeting vitamin D needs to prevent preeclampsia and gestational diabetes has increased after being given education.